Effect of Welding Current on Properties and Microstructure of Aluminum/Nickel Resistance Spot Welding Joints - Ye, Fang; Wu, Jisi (International Journal of Materials Science and Technology Studies, 2025)
The importance of the nonferrous metal connection technology has become increasingly prominent due to its increasing application of the nonferrous metals in aerospace, portable electronic products, new energy vehicles. Aluminum / nickel dissimilar metals were welded by micro-resistance spot welding, which can effectively reduce the formation of brittle intermetallic compounds between joints, so as to improve the performance of joint. Microstructure analysis and tensile shear tests were performed on the joints, influence of welding current on microstructure and properties of nugget were explored. The results suggest that with the increase of welding current, the tensile shear force of the welded joints could initially increased and then decreased. With the maximum tensile shear force reached 101.25 N at a welding current of 3.6 kA, a welding time of 130 ms and a welding pressure of 120 N. And there was almost no intermetallic compound in the joint.